2022
DOI: 10.1021/acs.est.2c00686
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Experimental and Computational Studies of Hydroxyl and Sulfate Radical-Mediated Degradation of Simple and Complex Organic Substrates

Abstract: Persulfate (PS)-based advanced oxidation processes (AOPs) have been promoted as alternatives to H2O2-based AOPs. To gauge the potential of this technology, the PS/Fe­(II) and Fenton (H2O2/Fe­(II)) processes were comparatively evaluated using formate as a simple target compound and nanofiltration concentrate from a municipal wastewater treatment plant as a complex suite of contaminants with the aid of kinetic modeling. In terms of the short-term rate and extent of mineralization of formate and the nanofiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Since Anipsitakis and Dionysiou first reported that Fe(II) added to a PMS solution could degrade 2,4-dichlorophenol, the Fe(II)/PMS system has received much attention. The transformation of the target compound in Fe(II)/PMS systems typically exhibits a rapid stage lasting minutes, followed by a much slower stage. ,,, It has been suggested that the rapid stage proceeds via outersphere electron transfer from Fe(II) to PMS to give SO 4 •– or Fe IV =O (reactions or ), which dominates target removal with the final products of SO 4 2– and Fe(III). ,,,, Because the reactivity of Fe(III) toward PMS is too weak to sustain the reaction, ,,, further addition of Fe(II) is required to achieve complete degradation of the target compounds, which results ultimately in generation of excessive iron sludge when the effluent is returned to neutral pH. In addition, the working pH range is limited to the range of 3.0–3.5, the lower end of which is to maintain reactivity and the upper end is to avoid coprecipitation of Fe(III) and Fe(II). , Obviously, improving the reactivity of Fe(III) toward PMS would benefit the development of a sustainable iron-based system in engineering applications. Fe false( normalII false) + normalHSO 5 normalSO 4 + Fe false( normalIII false) + OH k 1 a = ( 2.1 3.74 ) × 10 4 M 1 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Anipsitakis and Dionysiou first reported that Fe(II) added to a PMS solution could degrade 2,4-dichlorophenol, the Fe(II)/PMS system has received much attention. The transformation of the target compound in Fe(II)/PMS systems typically exhibits a rapid stage lasting minutes, followed by a much slower stage. ,,, It has been suggested that the rapid stage proceeds via outersphere electron transfer from Fe(II) to PMS to give SO 4 •– or Fe IV =O (reactions or ), which dominates target removal with the final products of SO 4 2– and Fe(III). ,,,, Because the reactivity of Fe(III) toward PMS is too weak to sustain the reaction, ,,, further addition of Fe(II) is required to achieve complete degradation of the target compounds, which results ultimately in generation of excessive iron sludge when the effluent is returned to neutral pH. In addition, the working pH range is limited to the range of 3.0–3.5, the lower end of which is to maintain reactivity and the upper end is to avoid coprecipitation of Fe(III) and Fe(II). , Obviously, improving the reactivity of Fe(III) toward PMS would benefit the development of a sustainable iron-based system in engineering applications. Fe false( normalII false) + normalHSO 5 normalSO 4 + Fe false( normalIII false) + OH k 1 a = ( 2.1 3.74 ) × 10 4 M 1 …”
Section: Introductionmentioning
confidence: 99%
“…PMS-based AOPs have several technical advantages over traditional H 2 O 2 -based AOPs. PMS in its stabilized form (as the complex, 2KHSO 5 ·KHSO 4 ·K 2 SO 4 ) is more convenient to transport and store and is more efficiently utilized in AOPs compared to H 2 O 2 . , PMS-based AOPs are less sensitive to dissolved water constituents (except for chloride) and have a broader working pH range. Due in part to its asymmetric molecular structure, PMS is more easily activated to reactive oxygen species than is H 2 O 2 . , Numerous physicochemical means of PMS activation have been proposed, including those mediated by transition metal ions, metal oxides, carbonaceous materials, and energy sources (e.g., light, heat, and electricity). Of the transition metals, iron is readily available, cheap, and environmentally benign, and therefore is the preferable activator in practice. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Notably, a certain degree of decline (13.9%) was observed for SnZVI@PBC/PS system after further increasing PS amount to 8 mM ( Fig. 7 H ), which was due to that superfluous PS could quench the generated by generating with lower redox potential ( 73 ), and self-scavenging reactions among the excessive also existed ( 70 ).…”
Section: Resultsmentioning
confidence: 98%